Cardiopulmonary exercise test in medical and biological practice (literature review) - A. B. Kiryanov; I. S. Kozhevnikova; A. A. Farkova; N. Yu. Anikina; E. V. Yurieva; A. I. Amelina (Acta Biomedica Scientifica, 2024)
Most tests assess physiology at rest, whereas many symptoms occur with physical exertion, and physical activity is an integral part of healthy functioning and quality of life of a person. Today, cardiopulmonary exercise testing is considered the standard for identifying exercise limitations and differentiating their causes.Cardiopulmonary exercise testing is widely used in both basic and the latest research from cardiology and pulmonology to neurology and hematology and has great prognostic value. Cardiopulmonary exercise testing is considered the gold standard for non-invasive assessment of the cardiopulmonary system and physical performance. This study has become even more relevant and in demand due to the COVID-19 outbreak; now it plays an important role in the clinical assessment of recovering patients who have had COVID-19.Numerous indicators recorded at each stage of the study, taken together, allow us to obtain a complete picture of the work of the cardiovascular, respiratory and muscular systems, as well as to study the characteristics of the metabolic response to stress.This article contains a review of the literature on the history of the application and development of the cardiopulmonary exercise testing, its physiological characteristics and a study of the literature concerning application of studied method in medicine over the past 5 years. The search and analysis of articles were carried out using the scientometric databases PubMed, ScienceDirect, Google Academia.The presented article may be useful for young specialists working in functional diagnostics, cardiology and pulmonology, as well as for researchers and postgraduates whose work involves application of the cardiopulmonary exercise testing method.